VIRTUAL LINGUISTIC LANDSCAPES OF JALAN H. IMAM MUNANDAR: ANALYZING COMMERCIAL TOPONYMY AND TOPONYMIC COMMODIFICATION FOR TEFL RESOURCES - Imelda Yance; Damsar; Bob Alfiandi; Katubi (JEE (Journal of English Education), 2026)
This study examines how commercial entities navigate official street renamings through their signage and digital mapping presence. Data were collected along an 8.5 km commercial corridor of Jalan H. Imam Munandar (formerly known as Jalan Harapan Raya) in Pekanbaru, and cross-verified via virtual mapping platforms. The structural analysis reveals four distinct naming formulas, namely new, legacy, hybrid, and legacy-plus-directional addresses. More importantly, this study unpacks a significant sociolinguistic phenomenon driven by toponymic attachment. Local business owners do not simply display the old street names as a location marker, but actively absorb the old toponyms into their identity, resulting in toponymic commodification. The transformation of old names into economic assets serves as a tool of linguistic resistance to maintain digital readability and community trust in the midst of administrative street name changes from above. From an applied linguistic perspective, these four structural formulas along with the phenomenon of commodification driven by toponymic attachment serve as a valuable pedagogical resource of TEFL. Language educators can leverage this authentic local LL corpus to foster EFL students' Critical Language Awareness and multimodal literacy. This study concludes that the virtual and physical linguistic landscape is a dynamic ideological space, where community identities and pragmatic business needs meet.